Peran Interaksi Guru-Siswa dan Gaya Belajar Siswa terhadap Disposisi Berpikir Kritis dalam Pembelajaran Fisika - Primadhani Setyaning Galih; Asmadi Alsa (Faculty of Psychology, Universitas Gadjah Mada, 2019)
This study aimed to empirically determine the role of teacher-student interaction and students’ learning styles in students’ disposition toward critical thinking in physics subject. Research participants were high school students of grade XI majoring in natural science. Sampling in this study was done using convenience sampling with sample size of 67 students (25 males and 42 females). Data collection method used in this study was survey using Disposition toward Critical Thinking in Physics Subject Scale, Teacher-student Interaction in Physics Subject Scale, and Learning Styles in Physics Subject Scale. Analysis of covariance with one covariate showed 1) there was a correlation between teacher-student interaction and students’ disposition toward critical thinking in physics subject (F = 37.199; ƞ2p = 0.375; p < 0.01) and 2) there was difference of disposition toward critical thinking in physics subjects between student with diverging, assimilating, accommodating, and converging learning styles (F = 6.870; ƞ2p = 0.249; p < 0.01). Post-hoc test was also done to further analyze the data. The findings are going to help improving quality of learning especially in the subject being studied by fostering wholesome teacher-student interaction and accommodating students’ learning styles.